2002
DOI: 10.1259/bjr.75.893.750435
|View full text |Cite
|
Sign up to set email alerts
|

Patient and staff exposure during endoscopic retrograde cholangiopancreatography

Abstract: Despite a number of efforts being put into the radiological protection of both patient and staff during interventional radiological (IR) procedures during recent years, information about radiation exposure during endoscopic retrograde cholangiopancreatography (ERCP) procedures remains scarce. The purpose of this study was to estimate both patient and staff radiation doses during therapeutic ERCP procedures by direct measurement and to compare these results with data from other IR procedures. For 54 patients, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 20 publications
(39 reference statements)
8
86
8
Order By: Relevance
“…A summary of the results (median, mean and maximum values) is shown in Table 1 In Table 2 and Figures 5 and 6, the comparison of median values of the quantities T (min) and KAP (Gy.cm 2 ) is presented, between the results of this study and the corresponding results of similar published data. [3,5,6,10,11]. This is reflected in our results too, as it can be seen in Table 1 and Figure 1, although a single, well-experienced endoscopist, using the same X-ray imaging system, performed all 1632 ECRP procedures.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…A summary of the results (median, mean and maximum values) is shown in Table 1 In Table 2 and Figures 5 and 6, the comparison of median values of the quantities T (min) and KAP (Gy.cm 2 ) is presented, between the results of this study and the corresponding results of similar published data. [3,5,6,10,11]. This is reflected in our results too, as it can be seen in Table 1 and Figure 1, although a single, well-experienced endoscopist, using the same X-ray imaging system, performed all 1632 ECRP procedures.…”
Section: Resultssupporting
confidence: 56%
“…Few studies that evaluate radiation exposure to staff during ERCP are found in the recent literature [11,[19][20][21][22][23]. These studies confirm that the radiation exposure to personnel undertaking ERCP is not negligible and radiation protection measures should be taken.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Typical staff dose readings for different types of procedures have been published in the literature [11,19,[26][27][28][29][30][31][32][33][34][35][36]. Depending on the type of procedure and the technique used, the operator dose, per procedure, ranges from 3 to 450 lSv at the neck over protective garments, from\0.1 to 32 lSv at the waist or chest under protective garments, and from 48 to 1280 lSv at the hand.…”
Section: Surveillance Of Occupational Dosementioning
confidence: 99%
“…[1] In the involve prolonged fluoroscopic screening and large number of image acquisitions and the effects. [6] Deterministic risks are those for which, beyond a dose threshold, the magnitude of damage is proportional to dose. Deterministic risks are of greater concern in interventional procedures because single fraction dose thresholds for transient and main erythema are of the order of 2-6 Gy, and 3 Gy for temporary epilation.…”
Section: Introductionmentioning
confidence: 99%